(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Electricity networks play a special role in the transmission and distribution of electricity. Almost all electricity is generated from the electricity grid. The main function of the power system is to supply electricity to consumers, that is, to transfer electricity from the place where it is generated to the place of its use. An improved understanding of the transmission and distribution of energy is the power system. The power system is a collection of power plants that are interconnected by these transmission lines and together provide electricity to consumers, the research results are presented [1].